Improving economic standards as one of the mechanisms for ensuring the stability of the banking system - Гончар, Юлія Юріївна; Сердюк, Любов Василівна (Eastern-European Journal of Enterprise Technologies, 2011)
The article highlights the dependence of the financial stability of the banking system from the bank's compliance with economic regulations and control it with the National Bank of Ukraine